“Drill, baby, drill” : right-wing populist culture wars in Aotearoa New Zealand 2023-25 : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts, Massey University, New Zealand - Carline, Alison Elizabeth (Massey University, 2026)
In March 2024, Aotearoa New Zealand’s newly elected coalition government, comprising the traditionally conservative National Party, libertarian ACT Party, and nationalist/populist New Zealand First Party, introduced legislation to override decades of environmental protection and expedite infrastructure projects, including mining on conservation land. Framed as a solution to bureaucratic red tape and economic stagnation, the Fast-track Bill provoked unprecedented opposition. The coalition Government’s response to critics was not primarily policy engagement but culture wars escalation, using anti-woke rhetoric to delegitimise environmental advocates, Māori rights activists, and scientific expertise. This thesis explores how the struggle for hegemonic dominance operates through culture wars discourse, revealing a strategic cooperation between neoliberal extractive interests and right-wing populism. A political speech by Resources Minister Shane Jones published to YouTube, audio-visual opinion pieces from three right-wing media figures, and eight one-on-one interviews with New Zealanders are analysed through critical discourse analysis and discourse theory. The analyses, informed by Hall’s encoding/decoding framework and theories of affect and fantasy, reveal how “woke” functions as an empty signifier capable of linking disparate issues into a unified threat to “commonsense”, giving voice to resentment and validating gleeful transgression. Culture wars rhetoric represents a faultline in contemporary New Zealand political discourse. It splinters potential progressive coalitions, delegitimises expertise, reframes democratic participation as obstructive, and provides the propaganda infrastructure through which environmental deregulation and resource extraction gain popular consent. With Resources Minister Shane Jones’ culture wars rhetoric as its anchoring focus, this thesis reveals dynamics that extend beyond one politician; Jones provides a lurid articulation of anti-woke sentiments that characterises the governing coalition’s broader approach to democratic contestation.
Keywords: culture wars; right-wing populism; neoliberalism; propaganda; encoding/decoding; critical discourse analysis; discourse theory; fantasmatic narratives; empty signifiers; antagonism; chains of equvalence; 470107 Media studies